Book Reviews (Rev. Anal. Numér. Théor. Approx., 1997)
Book reviews for:Partial Differential Equations and Functional Analysis, in Memory of Pierre Grisvard, edited by J. CEA, D. CHENAIS, G. GEYMONAT and J.-L. LIONS, Progress in Nonlinear Differential Equations and Their Applications, vol. 22, Birkhauser, Boston-Basel-Berlin, 1996, 264 pp., ISBN 0-8176-3839-3. Reviewed by R. Precup.YURI EGOROV, VLADIMIR KONDRATIEV, On Spectral Theory of Elliptic Operators, Operator Theory, vol. 89, Birkhauser, Basel, 1996, 338pp., ISBN 3-7643-5390-2. Reviewed by R. Precup.JAN van NEERVEN, The Asymptotic Behaviour of Semigroups of Linear Operators, Birkhauser Verlag, Basel-Boston-Berlin, 1996, 238pp. Reviewed by I. Rasa.LEON SIMON, Theorems on Regularity and Singularity of Energy Minimizing Maps, Lecture Notes in Mathematics, ETH Zurich, Birkhauser Verlag, Basel-Boston-Berlin, 1996,152 pp. Reviewed by D. Trif.Learning and Geometry: Computational Approaches, edited by DAVID KUEKER and CARL SMITH, Progress in Computer Science and Applied Logic, vol. 14, Birkhauser, Boston-Basel-Berlin, 1996. Reviewed by J. Robu.VLADIMIR F. DEMYANOV, ALEXANDER M. RUBINOV, Constructive Nonsmooth Analysis, Approximation & Optimization, vol. 7, Verlag Peter Lang, Frankfurt am Main, 416 pp. Reviewed by S. Cobzas.FRANCOISE CHAITIN-CHATELIN, VALERIE FRAYSSE, Lectures on Finite Precision Computations, SIAM, Philadelphia, 1996. Reviewed by I. Pavaloiu.NICHOLAS J. HIGHAM, Accuracy and Stability of Numerical Algorithms, SIAM, Philadelphia, 1996. Reviewed by E. Catinas.